A biocultural and intercultural response to firewood scarcity in rural communities inhabiting arid environments in Patagonia (Argentina) - Morales, Daniela; Molares, Soledad; Ladio, Ana H. (Ethnobiology and Conservation, 2017)
From an ecological perspective, the use of firewood species implies constant disturbance of the vegetation, but from a biocultural point of view the implications are more systemic and complex. The objective of this work was to make a comprehensive analysis of the biocultural characteristics of firewood plants used by two rural communities in arid Patagonia, with special emphasis on their tolerance of continuous extraction, recovery of the environment and cultural value. The study was carried out with 33 participants, and ethnobotanical information was collected on the use, preferences and attributes of species used, together with botanical-ecological information obtained from a bibliographical review. Of the 28 firewood species registered, 12 stood out as being preferred for firewood use. Native plants (66.6%) were generally preferred to exotic species (33.3%). Several ecological features of the preferred plants were noted, such as vegetative regeneration (42.9%), high levels of plasticity in relation to varying edaphic conditions (35.7%) and nitrogen fixation (14.3%). Most of these species also present a high level of utilitarian versatility, and are therefore multipurpose resources. These characteristics, of ecological and cultural importance, should be key criteria for the selection of species for forestry programmes related to the development of firewood plantations.